Protection of immunocompromised mice against lethal infection with Pseudomonas aeruginosa by active or passive immunization with recombinant P. aeruginosa outer membrane protein F and outer membrane protein I fusion proteins. - von Specht, B U (1995)
Recombinant outer membrane proteins (Oprs) of Pseudomonas aeruginosa were expressed in Escherichia coli as glutathione S-transferase (GST)-linked fusion proteins. GST-linked Oprs F and I (GST-OprF190-350 [GST linked to OprF spanning amino acids 190 to 350] and GST-OprI21-83, respectively) and recombinant hybrid Oprs (GST-OprF190-342-OprI21-83 and GST-OprI21-83-OprF190-350) were isolated and tested for their efficacy as vaccines in immunodeficient mice. GST-OprF-OprI protected the mice against a 975-fold 50% lethal dose of P. aeruginosa. Expression of GST-unfused OprF-OprI failed in E. coli, although this hybrid protein has been expressed without a fusion part in Saccharomyces cerevisiae and used for immunizing rabbits. The immune rabbit sera protected severe combined deficient (SCID) mice against a 1,000-fold 50% lethal dose of P. aeruginosa. Evidence is provided to show that the most C-terminal part of OprF (i.e., amino acids 332 to 350) carries an important protective epitope. Opr-based hybrid proteins may have implications for a clinical vaccine against P. aeruginosa.